2017
DOI: 10.1093/nutrit/nuw037
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and the built environment at different urban scales: examining the literature*

Abstract: The majority of people now live in an urban (or suburban) environment. The built (material) environment, its vehicular and pedestrian infrastructure, buildings, and public realm places, are the places used for working, living, and recreating. The environment currently favors and facilitates motorized vehicles generally, and private automobiles especially. The prioritization given to vehicles reduces opportunities for other, more active modes of travel such as walking and bicycling. Though the built environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 93 publications
3
47
0
Order By: Relevance
“…Walking is widely known as a sustainable mode of transportation with many social, environmental, and health benefits to the individuals and the society. Numerous studies have confirmed the role of walking on reducing obesity and other chronic diseases [52], reducing greenhouse gas emissions [53], and increasing social equity and economic vitality [54]. Despite these benefits, walking mode choice is declining in most American Cities and this trend, in large part, has to do with the built environment [55].…”
Section: Discussionmentioning
confidence: 99%
“…Walking is widely known as a sustainable mode of transportation with many social, environmental, and health benefits to the individuals and the society. Numerous studies have confirmed the role of walking on reducing obesity and other chronic diseases [52], reducing greenhouse gas emissions [53], and increasing social equity and economic vitality [54]. Despite these benefits, walking mode choice is declining in most American Cities and this trend, in large part, has to do with the built environment [55].…”
Section: Discussionmentioning
confidence: 99%
“…96 Availability of healthy food sources may also contribute, with studies showing less obesity in communities closer to grocery stores and more obesity in communities with more fast food restaurants or convenience stores. [95][96][97][98][99] Most studies evaluating the built environment have been cross-sectional, and therefore it is difficult to ascertain the extent to which aspects of the built environment are truly causal, or whether healthier individuals choose to live in specific environments (ie, self-selection bias). 98 Also, most data on the impact of the built environment on cardiovascular health are from HICs.…”
Section: Health Systemsmentioning
confidence: 99%
“…[95][96][97][98][99] Most studies evaluating the built environment have been cross-sectional, and therefore it is difficult to ascertain the extent to which aspects of the built environment are truly causal, or whether healthier individuals choose to live in specific environments (ie, self-selection bias). 98 Also, most data on the impact of the built environment on cardiovascular health are from HICs. The health impact of many aspects of the built environment may vary with context, and to date, there is a paucity of data from MICs and LICs to inform global policy.…”
Section: Health Systemsmentioning
confidence: 99%
“…HS patients have been found to be 17 times more likely to be obese compared to controls [14], and obesity may play a role in disease severity [15, 16]. The immediate surrounding environment of LSES patients can contribute to weight status [17]. Neighborhoods may be less walkable due to poor infrastructure or safety concerns, and have an abundance of convenience stores and fast food establishments instead of grocery stores with fresh produce [18-20].…”
Section: Address Lifestyle Challengesmentioning
confidence: 99%